Ethnogenesis and Migrant Muslim Religious Life in Malaysia - Wong, Diana; Aziz, Arfan (Kontekstualita, 2013)
Abstrak: Dinamika kehidupan keagamaan dan pembentukan identitas etnis setelah Malaysia merdeka adalah titik awal dari tulisan ini. Pembangunan ekonomi Malaysia yang pesat di tahun 1970-an mengundang migrasi tenaga kerja Indonesia dan negara-negara Asia lainnya seperti India, Bangladesh dan Myanmar, yang mereka membawa bersama budaya religius dari tanah air mereka dan memberi perubahan signifikan dalam wacana keagamaan warga. Artikel ini berdasarkan penelitian yang telah dilakukan pada kehidupan keagamaan dua komunitas migran di Malaysia dan bertujuan untuk menggambarkan hubungan antara kehidupan keagamaan warga dengan para migran di bawah panji etnogenesis Melayu Islam yang berlangsung di bawah rezim negara-bangsa Malaysia. Meskipun migran dan warga negara adalah muslim, studi ini menunjukkan ârumahâ bagi kedua belah pihak, malah di gerakan misionaris transnasional, terutama, Jamaah Tabligh yang akan dijabarkan lebih lanjut dalam pembahasan artikel ini. Kata kunci: Kehidupan Keagamaan, Minoritas Migran, Etnogenesis.Abstract: The dynamics of religious life and the formation of ethnic identity after Malaysia independence is the starting point of this paper. Malaysiaâs rapid economic development in 1970s invites Indonesia labor migration and other Asian countries like India, Bangladesh and Myanmar, which then bring together with them the religious culture of their homeland and significant changes in the religious discourse of citizens. This article based on the research that has been conducted on religious lives of two migrant communities in Malaysia and aimed to describe the relationship between religious lives of citizens below the Islamic Malay ethno genesis which took place under the Malaysian nation-state regime. Although the migrants and citizens both are Muslims, this study shows âthe homeâ for both sides precisely in the transnational missionary movements, especially, Tablighi Jamaat which will be further elaborated after the next discussion of this article. Keywords: Religious life, Migran minority, Ethnogenesis.